The Gender Dimension of Occupational Exposure to Contagion in Europe - Piotr Lewandowski; Katarzyna Lipowska; Iga Magda (Institute of Labor Economics (IZA), 2020)
We study the gender dimension of occupational exposure to contagious diseases spread by the respiratory or close-contact route. We show that in Europe, women are more exposed to contagion, as they are more likely than men to work in occupations that require contact with diseases, frequent contact with clients, and high levels of physical proximity at work. Women are also more likely than men to be unable to work from home, which contributes to their increased exposure. Gender is a more important factor in workers' exposure to contagion than their education or age. This gender difference in exposure can be largely attributed to patterns of sectoral segregation, and to the segregation of women within sectors into occupations that require more interpersonal interactions. While workers in Southern European countries are the most exposed to contagion, the gender differences in exposure are greatest in the Nordic and Continental European countries.
Keywords: J01; I10; J44; 330; COVID-19; contagion; exposure to disease; gender; occupations; working from home